Factors Affecting Delivery Preference of Primigravida Women: A Qualitative Study - DEMİRCİ, NURDAN (My University, 2018)
Objective: The objective was to identify factors affecting the pregnancy, pregnancyperception and preference of delivery method of primigravida women, and to evaluate their experiencesand satisfaction regarding their deliveries. Material and Methods: This is a descriptivestudy using a qualitative method. The study was carried out at the gynecology and obstetrics departmentof a university hospital in Turkey. The study group was composed of 14 primigravidawomen 18-35 years old who had not undergone IVF treatment. All had become pregnant spontaneouslyand none had a high-risky pregnancy, pregnancy is not risky. Data were collected viasemi-structured interviews after which thematic analyses were performed. Results: At the endof interviews with pregnant women, three main themes (perception of pregnancy, perceptionof childbirth and experience of childbirth) and seven subthemes (state of willingness for pregnancy,emotional state during pregnancy, preference of childbirth and affecting factors, fearfrom childbirth, method and experience of childbirth) were generated. Conclusion: As a resultof research; it was found that a planned pregnancy affected the attitude towards pregnancy. Inaddition, feelings of the women towards their pregnancy changed throughout the pregnancy,while their delivery choices did not change; most wanted vaginal deliveries since they believedit was healthier. All of the pregnant women were afraid of delivery and this fear of childbirthaffected the preference of delivery.

Amaç: Çalışmanın amacı Primigravida gebelerin gebelik, doğum algısı, doğum yöntemi tercihlerini etkileyen faktörler, doğumlarına ilişkin deneyimleri ve memnuniyetlerini belirlemek. Gereç ve Yöntemler: Araştırma niteliksel yöntemin kullanıldığı tanımlayıcı bir çalışmadır. Araştırma, Türkiye’de bir üniversite hastanesinin Kadın Hastalıkları ve Doğum Polikliniğinde yapılmıştır. İVF tedavisi görmeyen/kendiliğinden gebe kalan, 18-35 yaş aralığında, gebeliği riskli olmayan 14 primigravida çalışma grubunu oluşturmuştur. Veriler, yarı yapılandırılmış görüşmelerle toplanmış ve tematik analiz gerçekleştirilmiştir. Bulgular: Gebeler ile yapılan görüşmeler sonucunda üç ana tema (gebelik algısı, doğum algısı ve doğum deneyimi), yedi alt tema (gebeliğin istenme durumu, gebelikteki duygusal durum, doğum tercihi ve etkileyen faktörler, doğum korkusu, doğum yöntemi ve doğum deneyimi) ortaya çıkmıştır. Sonuç: Araştırma sonucunda; gebeliğin planlı olmasının gebeliğe ilişkin duyguları etkilediği, gebelik ile ilgili duyguların gebelik süresince değiştiği, gebelerin çoğunun daha sağlıklı olduğunu düşündükleri için vajinal doğum istediği ve gebelik boyunca tercihlerinin değişmediği, gebelerin tümünün doğumdan korktuğu ve doğum korkusunun doğum tercihini etkilediği bulunmuştur.
Primigravida Gebelerin Doğum Tercihlerini Etkileyen Faktörler: Niteliksel Bir Araştırma
Keywords: Hemşirelik